The Impact of Organizing a Wedding Party during the Covid-19 Pandemic and the Role of Community Leaders through Character Education in the Village Hiang Angkasa Pura Kerinci - Fadilla Ulpa (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
Leaders have a very significant role in preventive action efforts, the spread of the Covid-19 Pandemic in the surrounding environment, this is related to the analysis of the impact of holding weddings in the Covid-19 pandemic and the role of leaders as role models in implementing health protocols in the community. Data collection techniques are in the form of literacy studies from several scientific journal references and book sources that are adapted to events in the field. The purpose of this study is to see how the impact of holding a wedding party and the role of community leaders in Angkasa Pura Village is. So that through the character education provided and exemplified by the leader, it is hoped that the community in the village can comply with the Covid-19 pandemic health protocol in organizing weddings.